“They need to see breastfeeding so that they know how to do it”: the construction of motherhood through Instagram brelfies - Paige E. Davis; Alex Bridger; Kirsty Budds (International Breastfeeding Journal)
Abstract Background An offshoot of selfie taking is the “Brelfie” – a self-image capturing breastfeeding. Brelfie images and accompanying text are particularly useful to understanding how parents see themselves in their role within the digital age. The aim of this research was to understand how women posting #brelfies construct breastfeeding, motherhood, and identity through this modality. Methods This study used content analysis to examine 173 Instagram posts consisting of 199 Instagram breastfeeding images. The first author used open coding to create three visual representations and seven visual categories (e.g. focus on mother, child or both) from the corpus of data. An inductive interpretive thematic analysis was then performed to investigate the accompanying in post texts. Results were then analysed using chi-square tests. Although England was most prevalent, the Instagram search gleaned posts from nine other countries and posters used eight different languages. Results Content analyses indicated three types of visual image (breastfeeding portrait, breastfeeding selfie, and breastfeeding baby portrait) were tagged as brelfies, this supported the seven visual themes. Textually, three themes were developed: Breastfeeding as a Natural and Magical Journey, Breastfeeding as Female Empowerment, and Breastfeeding as a Struggle with the Desire for Support and Normalization. When analysed, breastfeeding portraits were associated with captions around the theme of female empowerment. The themes of a natural magical journey and struggle for support and normalisation were not related to any of the types of photos. Non-English language text was associated with the theme of the struggle. Conclusions This research supports the idea that mothers depict breastfeeding as largely positive, but that there are still perceived barriers and a voiced need for support. The type of brelfie presented and the language/cultural origin of the text could inform their intended message, thus helping understand how the parents see themselves. Brelfies should be encouraged to post this media to potentially help signpost to other breastfeeding parents that they are not alone in their breastfeeding journey.